Validity and reliability of the Indonesian version of cyber bullying perpetration (CBP) and victimization (CBV) instruments - Umar, Nur Fadhilah; Nurdin, Nur Hidayat; Zulfiqri, Zulfiqri; Rafli, Muhammad (ProGCouns: Journal of Professionals in Guidance and Counseling, 2025)
This study aimed to examine the validity and reliability of the Indonesian adaptation of the Cyber Bullying Perpetration (CBP) and Cyber Bullying Victimization (CBV) scales originally developed by Lee et al. (2017). The adaptation process involved translation, back-translation, expert judgment, and pilot testing to ensure conceptual and cultural equivalence. The final instrument consisted of 18 items rated on a four-point Likert scale (1 = never to 4 = very often) and was administered to a sample of 389 undergraduate students aged 19–22 years from three provinces in Sulawesi, Indonesia. The scales measured three dimensions of cyberbullying behavior: verbal-written bullying, visual-sexual bullying, and social exclusion. Results of the reliability analysis showed high internal consistency, with Cronbach’s alpha and McDonald’s omega coefficients exceeding 0.80 across most indicators. Confirmatory Factor Analysis (CFA) further demonstrated acceptable model fit indices, confirming that the adapted scales were theoretically robust and empirically supported. Although certain items in the social exclusion subscale showed lower correlations, the overall instrument demonstrated strong psychometric properties. These findings indicate that the Indonesian version of the CBP and CBV scales is both valid and reliable, making it suitable for research and practical applications in higher education contexts. The study contributes to the development of culturally relevant tools for assessing cyberbullying, providing essential insights for prevention, intervention, and future research.